PENGARUH STRATEGI PROMOTION MIX TERHADAP KEPUTUSAN KONSUMEN PENGGUNA PASTAGIGI - AP, S Soedewo; Esti, Erna Atiwi jaya (Magister Manajemen Universitas Wisnuwardhana, 2018)
Abstract, Toothpaste Pesoden is a product for and can be used by everyone to clean and whiten teeth in order to beautify or beautify human beings. Produced by PT Unilever), in this case the company's desire is to increase sales of Pepsodent toothpaste products by promotion promotion approach (Promotion Mix) which influences consumer decisions. Therefore it is very important to do research that aims to find out the significant influence of promotion mix consisting of advertisement, direct marketing, interaction marketing, sales promotion, public relation and personal selling both simultaneously and partially to decision making by consumer, this is all to increase Product sale. Then by hypothesis test the influence of promotion mix variable simultaneously in can result that there is significant influence all variable in promotion mix to consumer decision. Advertising variables influence the most dominant significant to consumer decisions. Therefore, the company suggested in increasing sales should pay attention to promotion mix in relation to consumer decision. Keywords: Promotion Mix Strategy, Consumer Decision.